DESIGN FOR MANUFACTURING (DFM) UNTUK MEMINIMASI BIAYA PRODUKSI DAN KUALITAS (STUDI KASUS PALLET BOX FABRICATION SECTION PT SAPTAINDRA SEJATI) - Arvita Emarilis Intani (Operations Excellence: Journal of Applied Industrial Engineering, 2017)
PT. XYZ is manufacturing of automotive spare parts and non-automotive company, which produces several products such as Oil Seal, Tensioner, Gasket, Rubber Only and other products. To fulfill the commitment to the company, one of the ways is to eliminate waste in the production process in the company, is Rubber. From the rubber scrap, the largest percentage is Rubber chips expired. So related to the purpose of this research is to identify the presence of waste on the rubber, improvements in production planning and compare MRP, RCCP and CRP. The method that used in this research is the FTA (Fault Tree Analysis) and RCCP (Rough Cut Capacity Planning) with CPOF technique (Capacity Planning Overall Factors). The result is able to minimize the rubber chip is wasted due to past the shelf (expired).